MEDIASI RETURN ON ASSET PADA KEPUTUSAN PENDANAAN, KEPUTUSAN INVESTASI, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Miftahul Jannah Nur Setya Murni; Listiorini Listiorini; Muhammad Karya Satya (Universitas Dharmawangsa, 2023)
This study aims to determine the mediation of return on assets on funding decisions, investment decisions, and dividend policies in manufacturing companies on the Indonesia Stock Exchange. The type of approach in this research is associative quantitative with data collection using documentation studies and secondary data in the form of annual reports published by the company on the IDX's official website, www.idx.co.id. The research population is all manufacturing companies on the Indonesia Stock Exchange. The sampling technique using purposive sampling obtained a sample of 27 companies with the year of observation starting from 2017-2021 (5 years) so that 135 samples were obtained. The data analysis technique used in this study used path analysis with the SPSS v.26 program.The results of this study indicate that funding decision (DER), investment decision (TAG), dividend policy (DPR) and return on assets affect firm value (PBV). Funding decisions (DER), investment decisions (TAG) and dividend policy (DPR) affect return on assets. Return on assets mediates the effect of funding decisions (DER), investment decisions (TAG) and dividend policy (DPR) on firm value (PBV).